The Effects of Preventive Consultation With Elementary School Principals on Changing Teacher Staff Meeting Behaviors - Carr, Rey Alexander (Canadian Journal of Counselling and Psychotherapy, 2012)
Consultee-centered consultation with elementary school principals about staff meetings was shown to have a significant impact on changing teacher behaviour at staff meetings towards more effective group inter-action. This study provides much needed experimental evidence of the value of consultation processes in the schools and outlines the techniques used by the consultant. Problems in shifting counselor role from direct to indirect or preventive services are discussed.